The Concept of Measure in the 19Th Century Javanese: An Ethnomathematics Study - Ekowati, Venny Indria; Suwardi, Suwardi; Mulyani, Hesti; Floriasti, Tri Wahyuni; Awalin, Fatkurrohman Nur; Saputri, Ines Ika; Hadirman, Hadirman (International Journal of Business, Law, and Education, 2025)
This study investigates the traditional concepts and mathematical practices of the Javanese people as found in Serat Centhini Kamajaya volumes IX–XII, focusing on how they performed measurements. The research employs a qualitative ethnomathematical approach using a framework based on four key questions: where to look, how to look, what it is, and what it means. Data were drawn from the transliteration of Serat Centhini volumes IX–XII and analyzed using content analysis, triangulation, and pattern identification across six basic mathematical activities. The study identifies sixteen traditional Javanese measurement terms in Serat Centhini IX–XII, including sacengkang, lengen, sapungge, ula sawa, kilan, pêcak, sagêgêm, glintir, sairis, jodho, sakêpêl, saklêmuk, saontong, poros, pulukan, and tangkeb. These terms illustrate the close relationship between culture and mathematical reasoning. The findings highlight the embeddedness of mathematical concepts in Javanese cultural expressions and support the integration of ethnomathematics into culturally responsive education.